2010
DOI: 10.1016/j.lwt.2009.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure processing on wheat dough and bread characteristics

Abstract: 21Microbial, physical and structural changes in high pressured wheat dough were studied 22 as a function of pressure level (50-250 MPa) and holding time (1-4 min). Thereafter, 23 selected conditions of high hydrostatic processing (HPP) were applied to bread dough 24 and the technological quality of the obtained breads was studied. The effect of HPP on 25 wheat dough was investigated by determining microbial population (total aerobic 26 mesophilic bacteria, moulds and yeasts), color and mechanical and texture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 24 publications
5
37
0
1
Order By: Relevance
“…The effect of HPP on microorganisms have been studied intensively showing that HPP is a very good technique for microbial inactivation (Daryaei & Balasubramaniam, ) although higher pressure levels and times have been used as compared to the ones employed in our study. Bárcenas et al () found that mild treatment (100 MPa, 1 min) was enough to obtain good microbial inactivation in bread dough. We obtained a significant microbial count reduction in cookie dough after 2 min at the lowest pressure (100 MPa).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of HPP on microorganisms have been studied intensively showing that HPP is a very good technique for microbial inactivation (Daryaei & Balasubramaniam, ) although higher pressure levels and times have been used as compared to the ones employed in our study. Bárcenas et al () found that mild treatment (100 MPa, 1 min) was enough to obtain good microbial inactivation in bread dough. We obtained a significant microbial count reduction in cookie dough after 2 min at the lowest pressure (100 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…The total color change (Δ E ) values (Table ) indicate that there was a statistically significant difference ( p < .05) between all samples except for the sample treated at 400 MPa which was statistically similar to the sample treated at 200 MPa. Bárcenas et al () have found that not time but intensity of pressure increased the total change of color (Δ E ) of wheat dough (bread). The whiteness index (WI) was also affected by HPP treatments (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…After the process, microbial counts (mesophilic bacteria, yeasts, molds) were reduced considerably in the dough; there were changes in color and structure, and gas distribution into the dough was more homogeneous. However, at 50 MPa there were some minor changes in proteins, indicating that higher pressure is required to modify starch [7].…”
Section: Grains and Other Productsmentioning
confidence: 97%
“…When treated by 500 MPa, small cavities and gaps occurred in the starch granule. The phenomenon might be attributed to the starch gelatinization and protein denaturation during the PHHP treatment (Bárcenas et al 2010).…”
Section: Morphologic Changes Of Brown Rice By Phhpmentioning
confidence: 99%